Cathodic activated stainless steel mesh as a highly active electrocatalyst for the oxygen evolution reaction with self-healing possibility - Zhang, Gui Rong; Shen, Liu Liu; Schmatz, Patrick; Krois, Konrad; Etzold, Bastian J.M. (Journal of Energy Chemistry, 2020)
The oxygen evolution reaction (OER) represents one of the major bottlenecks for broad-based applications of many clean energy storage/conversion technologies. The key to solving this problem lies in developing high-performing, cost effective and stable catalysts for the OER. Herein, we demonstrate that ubiquitous stainless steel mesh (SSM) materials activated by a facile cathodization treatment can be employed as a high performing OER catalyst, as showcased by the impressively low overpotentials of 275 and 319 mV to reach the benchmark current densities of 10 and 100 mA cm−2 (1.0 M KOH), respectively. Cathodized SSM also exhibits excellent performance in a two-electrode water electrolyzer, which requires a low cell voltage of 1.58 at 10 mA cm−2 and outperforms many of water electrolyzers using earth-abundant OER catalysts. Moreover, cathodized SSM with minor performance degradation after the stability test can also be readily healed by subjecting it to an additional cathodization treatment. It is disclosed that the superior performance of cathodized SSMs stems from the surface enrichment of OER active Ni (oxy)hydroxide, facile gas-bubble removal and transportation over the unique mesh-structured surfaces, while the abundant reservoir of nickel in the bulk allows healing of the catalyst by a facile cathodization.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Cathodization; Mass transfer limitation; Oxygen evolution reaction; Self-healing; Stainless steel mesh; Water splitting